Pengaruh Kegiatan Paper Quilling terhadap Kemampuan Motorik Halus Anak Usia 5-6 Tahun di TK Al-Fur’qon Desa Pedamaran Kabupaten Ogan Komering Ilir - Wini Malinda; Muhtarom Muhtarom; Elsa Cindrya (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study investigates the impact of paper quilling activities on improving the fine motor skills of children aged 5–6 years at Al-Furqon Kindergarten in Pedamaran Village, Ogan Komering Ilir Regency. The research employs an experimental approach, which is a method designed to examine cause-and-effect relationships determined by the researcher. This study applies a Pre-Experimental method with a One Group Pretest-Posttest Design, where one group of participants is observed before and after treatment. The research population consists of 13 children aged 5–6 years enrolled in group B at Al-Furqon Kindergarten. Data collection was conducted through observation to measure changes in children's fine motor abilities before and after the implementation of paper quilling activities.The findings reveal a notable enhancement in fine motor development following the intervention. Prior to the activity, 2 children demonstrated low fine motor ability, 3 children showed moderate skills, and 8 children achieved higher scores. After participating in paper quilling sessions, all 13 children reached the “very well-developed” category, indicating marked improvement. These results demonstrate that paper quilling activities contribute significantly to strengthening children's fine motor coordination and precision. Thus, engaging children in paper quilling proves to be an effective strategy for supporting motor skill development in early childhood education settings.